2021
DOI: 10.1080/1461670x.2021.1944280
|View full text |Cite
|
Sign up to set email alerts
|

Belgian Journalists in Lockdown: Survey on Employment and Working Conditions and Representations of Their Role

Abstract: The COVID-19 pandemic has highlighted an important paradox: it has reminded us of the importance of the news media and the central place it occupies in the public space in times of crisis. At the same time, it has showed the major difficulties the industry faces in Belgium and elsewhere in the world. The lockdown disrupted the employment and practices of many journalists in ways that may reveal the contemporary tensions between professional identity and working conditions more clearly than in average news cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Emerging research on the working and living conditions of journalists during the pandemic suggests an intensification of preexisting trends, such as income losses and increased workloads, with the added difficulty of working from home during lockdowns (Rick & Hanitzsch, 2023). Journalists with children, and women more so than men, perceived reconciling family life and domestic work with professional activities in the same physical space as a major challenge (Libert et al, 2022). Feelings of loneliness and isolation were pervasive, as the journalists missed interacting with colleagues and sources (ibid.).…”
Section: Journalistic and Cultural Work During The Pandemicmentioning
confidence: 99%
“…Emerging research on the working and living conditions of journalists during the pandemic suggests an intensification of preexisting trends, such as income losses and increased workloads, with the added difficulty of working from home during lockdowns (Rick & Hanitzsch, 2023). Journalists with children, and women more so than men, perceived reconciling family life and domestic work with professional activities in the same physical space as a major challenge (Libert et al, 2022). Feelings of loneliness and isolation were pervasive, as the journalists missed interacting with colleagues and sources (ibid.).…”
Section: Journalistic and Cultural Work During The Pandemicmentioning
confidence: 99%
“…Almost unanimously in both countries, journalists reported limited access to information confirming relevant research (Libert et al, 2022). Social distancing and lockdowns made it very difficult for journalists to access their sources.…”
Section: Limited Access To Informationmentioning
confidence: 99%
“…Social isolation means that workers feel personally disconnected from coworkers and their supervisor. A survey of Belgian journalists during COVID found many reported social isolation [11], a feeling repeated in many other settings [12]. It has been found that the type of job can moderate feelings of isolation.…”
Section: Team Member Growth and Fulfillmentmentioning
confidence: 99%
“…A possible outcome of the broad shift to WFH is increased acceptance of the blurring of family into work times and spaces [18]. However, the flexibility that comes with telework can also cause frustration because of the difficulties in dividing time between work and family [11,18,19] and an inability to know when to stop working [7,19]. It seems like a paradox, where on one side teleworkers feel less stressed working from home in comparison to working from the office because of their ability to have more control.…”
Section: Team Member Growth and Fulfillmentmentioning
confidence: 99%
See 1 more Smart Citation